(3WHbGJ GdTGaYjI GdUZQis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPG oeNJUQ dWHa aj JGQjN GdabgGA GdTGaYjjf LeYfG ajg eG ChQO aj cJGHfG GdcHjQ ef GdCSeGA , hEbJUQfG ajg Ydi fHP jSjQI s
(3BNQgG (B:s
(3gPG BNQ GdoeNJUQ GdCUZQ ef cJGHfG WHbGJ GdTGaYjjf hGJab GdaQGZ efg SfI (B746(3, HOeTb s
(3GfXQ Qbe (B315 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs